Pediatric testicular microlithiasis: a review of epidemiology, risk associations and management - Zitouni, Hayet; Dghaies, Rim; Kechiche, Nahla; Mhiri, Riadh (Frontiers in Pediatrics, 2026)
Testicular microlithiasis is defined by the presence of five or more randomly distributed hyperechogenic microliths, each measuring less than 3 mm in diameter, observed in a single ultrasound scan. Histologically, testicular microlithiasis is characterized by multiple laminated calcifications within seminiferous tubules. The underlying cause of these calcifications is not yet fully understood. The exact prevalence of testicular microlithiasis in children remains uncertain and continues to be a topic of debate. These calcifications can occur either independently or in association with various benign conditions, malignant pathologies, or specific congenital disorders. Whether these associations are causal or coincidental remains unclear. The aim of this study is to review the prevalence of TM in children, with emphasis on its histological characteristics, underlying mechanisms, and contributing factors, and to investigate its association with testicular malignancy in order to propose a pragmatic follow-up approach based on current guideline recommendations.